Stimulants Vs Behavior Therapy in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
A 14-month randomized clinical trial in 579 children, aged 7 to 9.9 years, with ADHD Combined type, compared the effects of four different treatment programs (Multimodal Treatment Study).